ANALISIS DAN PERANCANGAN SISTEM INFORMASI LAYANAN PESERTA PELATIHAN BERBASIS WEB PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN PROVINSI JAMBI - Nasution, Indra Kusuma; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2019)
Lembaga Penjaminan Mutu Pendidikan (LPMP) carries out education and secondary education qualityassurance in the province based on the policy of the Minister of Education and Culture. In carrying outits main tasks, LPMP has various program activities such as Coordination Meeting (CoordinationMeeting), Training, Workshop. At present, the procedure is applied to participants who come to LPMP toparticipate in various types of conventional training, meaning from starting to receiving participants,arranging classes, determining rooms, and storing documents, not yet properly recorded. While onarchiving paper only contains storage of hardcopy documents. to change the participant acceptancemethod used today, that is, the conventional method becomes a computerized and WEB-based archiveadmission method. In approving the system, acceptance of participants based on this website uses webbased programming using PHP and MySQL. Regarding the purpose of this study is to study and analyzethe problems that exist in the acceptance of participants in the activity and information systems for WEBbased training participants